Generation Z’s Intention to Give Online Alms: An Integration of UTAUT, Religiosity, and Alms Literacy - Putri Azka Sabilana; Dewita Puspawati (Economics and Digital Business Review, 2026)
The evolution of digital technology has revolutionized how Generation Z in Indonesia engages in charitable acts through online avenues. This research examined the impact of charity literacy, religiosity, and UTAUT elements (performance expectancy, effort expectancy, facilitating conditions, and social influence) on the intentions to donate online. A quantitative associative method was employed with 160 respondents from Generation Z, utilizing a 5-point Likert scale questionnaire and analyzed using PLS-SEM through SmartPLS 4.0. The findings revealed that performance expectancy and facilitating conditions significantly influenced online charitable intentions, whereas effort expectancy, social influence, religiosity, and charity literacy had no significant impact. These six factors accounted for 38.3% of the variability in digital charity intentions. These results highlight the necessity for technological accessibility and sufficient resources to boost Generation Z's involvement in digital philanthropy while promoting the importance of charity literacy education and religious principles to enhance the significance of charitable practices.